Adding value to imperfect long-term animal monitoring data for conservation insight - S.D. Sarre; E.J. Stringer; R. Brawata; E. Carlson; R. Colley; E. Cook; B. Croak; L.I. Doucette; M. Hoehn; B. Howland; W.S. Osborne; S. Pulsford; et al. (Biological Conservation, 2026)

Quantifying taxon-specific habitat connectivity requirements of urban wildlife using structured expert judgement - Stephanie K. Courtney Jones; Luke S. O'Loughlin; Danswell Starrs; Jacinta E. Humphrey; Stephanie A. Pulsford; Hugh Allan; Matt Beitzel; Kym Birgen; Suzi Bond; Jenny Bounds; Deborah Bower; Renee Brawata; et al. (Biological Conservation, 2025)

Freshwater early life growth influences partial migration in populations of Dolly Varden (Salvelinus malma malma) - Christie M. Morrison; Colin P. Gallagher; Keith B. Tierney; Kimberly L. Howland (Polar Biology, 2021)
Populations of northern Dolly Varden ( Salvelinus malma malma ) exhibit partial seaward migration, yet little is known about this phenomenon in Dolly Varden populations. Our study analyzed data from three different Dolly Varden populations in the western Canadian Arctic in order to determine if: (1) differences in size-at-first seaward migration exist between fish that migrate at early and late ages among populations inhabiting different river systems, and (2) annual growth influences anadromous or resident life history choice. Otolith strontium analysis and back-calculation were used to determine age- and size-at-first seaward migration, respectively. Differences in age- and size-at-first seaward migration were determined across river system and migration age. Back-calculated fish lengths were compared using a mixed effect model to determine how early growth influences migratory tactics (early or late aged smolt, or resident). Our results indicate that fish exhibiting faster early growth migrated in earlier years and at smaller sizes than slower growing fish, however size- and age-at first seaward migration varied by river system. Faster growing Dolly Varden tended to become either residents or early smolts, while slower growth was associated with smolting later in life. This is contrary to life history theory where the fastest growing fish in a population should mature as a resident. Our results indicate factors other than growth may be influencing life history ‘decisions’ in Dolly Varden. Future work on growth efficiencies and metabolic rates is needed to assess how they affect migratory behaviours.

Antipsychotic potential of the type 1 cannabinoid receptor positive allosteric modulator GAT211: preclinical in vitro and in vivo studies - Dan L. McElroy; Andrew J. Roebuck; Gavin A. Scott; Quentin Greba; Sumanta Garai; Eileen M. Denovan-Wright; Ganesh A. Thakur; Robert B. Laprairie; John G. Howland (Psychopharmacology, 2021)

Left atrial mechanics and aortic stiffness following high intensity interval training: a randomised controlled study - Navazh Jalaludeen; Samuel J. Bull; Katrina A. Taylor; Jonathan D. Wiles; Damian A. Coleman; Lucinda Howland; Omar Mukhtar; Joseph Cheriyan; Ian B. Wilkinson; Rajan Sharma; Jamie M. O’Driscoll (European Journal of Applied Physiology, 2020)

Effects of the T-type calcium channel antagonist Z944 on paired associates learning and locomotor activity in rats treated with the NMDA receptor antagonist MK-801 - Andrew J. Roebuck; Wendie N. Marks; Max C. Liu; Nimra B. Tahir; Nadine K. Zabder; Terrance P. Snutch; John G. Howland (Psychopharmacology, 2018)

Assessing conservation risks to populations of an anadromous Arctic salmonid, the northern Dolly Varden (Salvelinus malma malma), via estimates of effective and census population sizes and approximate Bayesian computation - Les N. Harris; Friso P. Palstra; Robert Bajno; Colin P. Gallagher; Kimberly L. Howland; Eric B. Taylor; James D. Reist (Conservation Genetics, 2017)

MK-801-induced impairments on the trial-unique, delayed nonmatching-to-location task in rats: effects of acute sodium nitroprusside - Jessica L. Hurtubise; Wendie N. Marks; Don A. Davies; Jillian K. Catton; Glen B. Baker; John G. Howland (Psychopharmacology, 2017)

A 3D stereo camera system for precisely positioning animals in space and time - Nicholas B. W. Macfarlane; Jonathan C. Howland; Frants H. Jensen; Peter L. Tyack (Behavioral Ecology and Sociobiology, 2015)

Microbial Reduction of 9-Fluorenone to 9-Hydroxyfluorene in Carbon-Filtered Water: A Confounding Factor in an Aquatic Bioassay of 9-Fluorenone with Larvae of the Midge, Chironomus tentans (Fabr.) - P. W. O’Keefe; O. Ekabo; E. Braun-Howland; D. Swarr; B. Stockholm (Bulletin of Environmental Contamination and Toxicology, 2005)